322PThree-year overall survival update from the PACIFIC trial. (24th November 2019) - Wu, Y-L; Gray, J E; Villegas, A; Daniel, D B; Vicente, D; Murakami, S; Hui, R; Kurata, T; Chiappori, A; Lee, K H; Cho, B C; Planchard, D; et al.
Abstract: Background: In the phase 3 PACIFIC study of patients with unresectable, Stage III NSCLC without progression after chemoradiotherapy (CRT), durvalumab demonstrated significant improvements versus placebo in the primary endpoints of progression-free survival (HR, 0.52; 95% CI, 0.42–0.65; P < 0.0001) and overall survival (OS; HR, 0.68; 95% CI, 0.53–0.87; P = 0.00251). Safety was similar and durvalumab had no detrimental effect on patient-reported outcomes. Here, we report 3-year OS rates for all patients randomized in the PACIFIC study. Methods: Patients with WHO PS 0/1 (any tumor PD-L1 status) who received ≥2 cycles of platinum-based CRT were randomized (2:1), 1–42 days following CRT, to receive durvalumab 10 mg/kg intravenously every 2 weeks or placebo, up to 12 months, and stratified by age, sex, and smoking history. OS was analyzed using a stratified log-rank test in the ITT population. Medians and OS rates at 12, 24 and 36 months were estimated by Kaplan-Meier method. Results: In total, 713 patients were randomized of whom 709 received treatment (durvalumab, n = 473; placebo, n = 236). The last patient had completed the protocol-defined 12 months of study treatment in May 2017. As of January 31, 2019 (data cutoff), 48.2% of patients had died (44.1% and 56.5% in the durvalumab and placebo groups, respectively). The median duration of follow-up was 33.3 months (range, 0.2–51.3). Updated OS remained consistent with that previously reported (stratified HR 0.69, 95% CI, 0.55–0.86), with the median not reached (NR; 95% CI, 38.4 months–NR) with durvalumab versus 29.1 months (95% CI, 22.1–35.1) with placebo. The 12-, 24- and 36-month OS rates with durvalumab and placebo were 83.1% versus 74.6%, 66.3% versus 55.3%, and 57.0% versus 43.5%, respectively. After discontinuation, 43.3% and 57.8% in the durvalumab and placebo groups, respectively, received subsequent anticancer therapy (9.7% and 26.6% subsequently received immunotherapy). OS subgroup results will be presented. Conclusions: Updated OS data from PACIFIC, including 3-year survival rates, underscore the long-term clinical benefit with durvalumab following CRT and further establish the PACIFIC regimen as the standard of care in this population. Clinical trial identification: NCT02125461. Editorial acknowledgement: Medical writing support during the preparation of this abstract, which was in accordance with Good Publication Practice (GPP3) guidelines, was provided by Hashem Dbouk, of Cirrus Communications (Macclesfield, UK), an Ashfield company, and was funded by AstraZeneca. Legal entity responsible for the study: AstraZeneca. Funding: AstraZeneca. Disclosure: Y-L. Wu: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self): Eli Lilly; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Roche; Honoraria (self): Pierre Fabre; Honoraria (self): Pfizer; Honoraria (self): Sanofi; Advisory / Consultancy: Merck; Advisory / Consultancy, Research grant / Funding (institution): Boehringer Ingelheim. J.E. Gray: Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy: Janssen; Honoraria (self), Advisory / Consultancy: Celgene; Honoraria (self), Advisory / Consultancy: Takeda; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Genentech; Honoraria (self), Advisory / Consultancy: Eli Lilly; Honoraria (self), Advisory / Consultancy: Triptych Health Partners; Research grant / Funding (institution): Array; Research grant / Funding (institution): Merck; Research grant / Funding (institution): Epic Sciences; Research grant / Funding (institution): BMS; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): Trovagene; Research grant / Funding (institution): Loxo; Research grant / Funding (institution): Blueprint; Research grant / Funding (institution): Novartis. A. Villegas: Honoraria (self): AstraZeneca; Honoraria (self): Seattle Genetics. D.B. Daniel: Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): E R Squibb & Sons; Research grant / Funding (institution): Boehringer Ingelheim; Research grant / Funding (institution): Genentech; Research grant / Funding (institution): Eli Lilly; Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Celgene; Research grant / Funding (institution): Roche; Research grant / Funding (institution): E1 Therapeutics. D. Vicente: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: BMS; Advisory / Consultancy: Merck; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Roche. S. Murakami: Research grant / Funding (institution): Takeda; Honoraria (self): AstraZeneca; Honoraria (self): Chugai; Honoraria (self): Ono; Honoraria (self): Merck Sharp and Dohme. R. Hui: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Merck Sharp and Dohme; Honoraria (self), Advisory / Consultancy: Novartis; Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: Bristol-Myers Squibb. T. Kurata: Honoraria (self), Research grant / Funding (institution): AstraZeneca; Honoraria (self): Ono; Honoraria (self), Research grant / Funding (institution): Bristol Myers Squibb; Honoraria (self), Research grant / Funding (institution): Chugai; Honoraria (self): Lilly; Honoraria (self): Boehringer Ingelheim; Honoraria (self), Research grant / Funding (institution): MSD. A. Chiappori: Speaker Bureau / Expert testimony: Genentech; Speaker Bureau / Expert testimony: Merck; Speaker Bureau / Expert testimony: Takeda; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Novartis; Speaker Bureau / Expert testimony: Boehringer Ingelheim; Speaker Bureau / Expert testimony: Celgene; Research grant / Funding (institution): Bristol Myers Squibb. B.C. Cho: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Research grant / Funding (institution): Bayer; Research grant / Funding (institution): MOGAM Institute; Research grant / Funding (institution): Dong-A ST; Research grant / Funding (institution): Champions Oncology; Advisory / Consultancy, Research grant / Funding (institution): Janssen; Advisory / Consultancy, Research grant / Funding (institution): Yuhan; Advisory / Consultancy, Research grant / Funding (institution): Ono; Research grant / Funding (institution): Dizal Pharma; Advisory / Consultancy, Research grant / Funding (institution): MSD; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Roche; Advisory / Consultancy: BMS; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Eli Lilly; Advisory / Consultancy: Takeda; Shareholder / Stockholder / Stock options: TheraCanVac Inc. D. Planchard: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: BMS; Advisory / Consultancy: Celgene; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer; Advisory / Consultancy: MSD; Advisory / Consultancy: Roche; Advisory / Consultancy: prIME Oncology; Advisory / Consultancy: PeerCME. L. Paz-Ares: Leadership role: Genomica; Honoraria (self), Travel / Accommodation / Expenses, Spouse / Financial dependant: Roche; Honoraria (self), Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Travel / Accommodation / Expenses: MSD; Honoraria (self), Travel / Accommodation / Expenses: BMS; Honoraria (self), Travel / Accommodation / Expenses: Lilly; Honoraria (self), Travel / Accommodation / Expenses, Spouse / Financial dependant: Pfizer; Honoraria (self): Merck Serono; Honoraria (self): Pharma Mar; Honoraria (self), Spouse / Financial dependant: Novartis; Honoraria (self): Celgene; Honoraria (self): Sysmex; Honoraria (self), Spouse / Financial dependant: Amgen; Honoraria (self): Incyte; Spouse / Financial dependant: Ipsen; Spouse / Financial dependant, Leadership Role: European Medicines Agency; Spouse / Financial dependant: SERVIER; Spouse / Financial dependant: Sanofi; Spouse / Financial dependant: Merck. C. Faivre-Finn: Advisory / Consultancy, Speaker Bureau / Expert testimony, To institution: AstraZeneca. J.F. Vansteenkiste: Honoraria (self), Research grant / Funding (institution): MSD; Honoraria (self): AstraZeneca; Honoraria (self): Boehringer Ingelheim; Honoraria (self): Eli-Lilly; Honoraria (self): Apotex; Honoraria (self): Roche. M. Taboada: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. P.A. Dennis: Shareholder / Stockholder / Stock options, Full / Part-time employment: AstraZeneca. M. Özgüroğlu: Advisory / Consultancy: Janssen. S.J. Antonia: Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: AstraZeneca; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: BMS; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Merck; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Boehringer Ingelheim; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Novartis; Honoraria (self), Advisory / Consultancy: Memgen; Advisory / Consultancy, Travel / Accommodation / Expenses: FLX Bio; Honoraria (self), Shareholder / Stockholder / Stock options: CBMG. All other authors have declared no conflicts of interest.